Enrichment Strategy for Systemic Sclerosis Clinical Trials Targeting Skin Fibrosis: A Prospective, Multiethnic Cohort Study - Carina Mihai; Rucsandra Dobrota; Shervin Assassi; Maureen D. Mayes; Oliver Distler (ACR Open Rheumatology, 2020)
Objective The modified Rodnan skin score (mRSS) is often used as a primary outcome measure in systemic sclerosis (SSc) randomized clinical trials (RCTs). Previous cohort studies with predominantly European Caucasian patients showed that setting an upper limit of mRSS as a selection criterion for RCTs leads effectively to enrichment with progressive patients. This study aimed to demonstrate this effect in an ethnically diverse cohort, rich in patients positive for anti‐RNA polymerase III antibodies (Pol3). Methods We selected from the Genetics versus Environment in Scleroderma Outcomes Study (GENISOS) cohort patients with diffuse cutaneous SSc (dcSSc), who had mRSS of 7 or more at inclusion and a documented mRSS after 12 ± 2 months. Progression of skin fibrosis was defined as an increase in mRSS greater than 5 points and 25% or more from baseline. To identify the optimal cutoff for the baseline mRSS yielding the highest sensitivity for progressive skin fibrosis, we developed ROC curves and logistic regression models with “progression” as the outcome variable and a binary variable of baseline mRSS cutoff point as predictor. Results We included 152 patients (age and disease duration [mean ± SD, years]: 48.7 ± 13.0 and 2.4 ± 1.5 respectively, 22.4% males, 34.2% Pol3‐positive). Seventeen patients (11.2%) had skin fibrosis progression after 12 ± 2 months. An mRSS cutoff of 27 or less had the highest probability of progression (odds ratio, 9.12; 95% confidence interval: 1.173‐70.851; P = 0.035; area under the curve, 0.652; sensitivity, 94%). Conclusion We demonstrated in an ethnically diverse cohort of patients with early dcSSc and with a high proportion of patients who are Pol3‐positive that setting an upper limit of the mRSS as a selection criterion leads effectively to cohort enrichment with progressors.